2013
DOI: 10.1186/1471-2431-13-45
|View full text |Cite
|
Sign up to set email alerts
|

Long term effects of a health promotion intervention in low socioeconomic Arab- Israeli kindergartens

Abstract: BackgroundObesity is the most common chronic pediatric disease in westernized, especially low socioeconomic societies. We previously demonstrated the beneficial effects of a randomized prospective school-based health education program for low socioeconomic status Arab-Israeli kindergarten children.MethodsTo examine whether the effects of our program on nutrition and physical activity knowledge and preferences, anthropometric measures, and fitness persisted one year after the end of intervention.We were able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 19 publications
(29 reference statements)
0
36
0
2
Order By: Relevance
“…None of the other intervention types that did in fact use anthropometric measurements found an effect on BMI, with the exception of [31]. However Witt et al [35] found an effect on serum cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…None of the other intervention types that did in fact use anthropometric measurements found an effect on BMI, with the exception of [31]. However Witt et al [35] found an effect on serum cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the interventions were found to be effective at short‐term follow‐up, most of the studies providing results at long‐term follow‐up failed to show significant effects in changing child weight‐related outcomes. Only five studies were effective at long‐term follow‐up (Bocca, Corpeleijn, Stolk, & Sauer, ; Brotman et al., ; Fitzgibbon et al., ; Nemet et al., ; Stark et al., ), all of which were initiated during the preschool years rather than in infancy. Moreover, three of these five studies with the highest effect sizes at long‐term follow‐up included an additional general parenting skills and behaviors component (Bocca et al., ; Brotman et al., ; Stark et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that having booster sessions after the end of the intervention increases or maintains intervention effectiveness in the longer term by making the information better understood and reflected upon without decreasing participant motivation with prolonged sessions (Eyberg, Edwards, Boggs, & Foote, ; Nation et al., ). Interestingly, among the interventions included in the meta‐analysis, only three studies were found to be effective both at short‐term and long‐term follow‐ups (Bocca et al., ; Nemet, Geva, Pantanowitz, et al., ; Nemet et al., ; Stark et al., ), each of which targeted preschool children. Two of these three studies were conducted with children who were obese or overweight, and focused on general parenting skills in interactive sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Health promotion trial of Nemet et al recruited preschool‐aged Arab‐Israeli children (mean age 5.4, n = 203) in Israel . Eleven kindergarten schools were recruited from communities with low–socio‐economic status in central Israel.…”
Section: Resultsmentioning
confidence: 99%